How Workplace Compassion, Social Support, and Altruism in Predicting Retention among Employees in the Highly Competitive Businesses - Fajri, Dzakwan Sabil Al; Alfareza, Muhammad; Satrio, Rio; Siddiq, Dedi Muhammad; Mamat, Mazlina (Jurnal Ekonomi dan Bisnis Digital, 2024)
Employee retention plays a very important role for companies because the decreasing number of employees who want to leave a job may have a good impact on the companies to achieve their organizational goals. The purpose of this study is to investigate the link between workplace compassion, social support, and altruism on employee retention in the context of highly competitive business sector. The respondents in this research include employees in competitive companies with a total of 250 respondents. The data were collected using paper-based questionnaires. Drawing on multiple linear regression analysis, validity testing, reliability testing and hypothesis testing (T Test), this research found that workplace compassion, social support, and altruism predict employee retention. This reseacrh provides strategic insight for companies in improving compassion, social support, and altruism to strengthen overall employees’ sense of home.